Evaluation of Mangrove Water Quality in Pancer Cengkrong, Trenggalek and Sine, Tulungagung, East Java, Indonesia Using Phytoplankton as Bioindicators - Satria Cahya Febriansyah; Luchman Hakim; Catur Retnaningdyah (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research